2019
DOI: 10.9734/acri/2019/v18i430142
|View full text |Cite
|
Sign up to set email alerts
|

Nigeria Government’s Expenditure on Economic and Social Service Development: A Canonical Correlation Analysis Approach

Abstract: The study examine the effect of Government’s expenditure on economic and social services development in Nigeria over the period of 1961 to 2018. The study used Canonical Correlation Analysis, the test carried out include; Structure Vector for Economic and social Service and Redundancy Index. The result reveals that strong positive relationship exists between national recurrent expenditure and economic service and Social service. The study also discover that Nigeria Government placed more emphasis on other econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The discoveries of their research showed the presence of a two-way direct long-run association among economic development in Pakistan and education. Similarly, our finding concurs with the investigation of (Becherair, 2014;Akano and Adams, 2019), that used the bound testing technique to confront the cointegration and error rectification models, produced within an autoregressive disseminated slack structure in an annual dataset for the time (1971 to 2011) to investigate if a long run harmony relationship exists between the significant schooling classifications and monetary development in Algeria.…”
Section: Discussion Of Findingssupporting
confidence: 88%
“…The discoveries of their research showed the presence of a two-way direct long-run association among economic development in Pakistan and education. Similarly, our finding concurs with the investigation of (Becherair, 2014;Akano and Adams, 2019), that used the bound testing technique to confront the cointegration and error rectification models, produced within an autoregressive disseminated slack structure in an annual dataset for the time (1971 to 2011) to investigate if a long run harmony relationship exists between the significant schooling classifications and monetary development in Algeria.…”
Section: Discussion Of Findingssupporting
confidence: 88%